Social norms and security and justice services for gender-based violence survivors in Nepal: Programmatic implications from a mixed-methods assessment - Cari Jo Clark; Brian Batayeh; Iris Shao; Irina Bergenfeld; Manoj Pandey; Sudhindra Sharma; Shikha Shrestha; Amritha Gourisankar; Anudeeta Gautam; Tehnyat J. Sohail; Holly Shakya; Grace Morrow; et al. (PLoS ONE, 2025)
Background Gender-based violence (GBV) is highly prevalent throughout the world. Only a small fraction of survivors seek help from security and justice (S&J) providers such as the police or courts, due in part to social norms that discourage help-seeking. The prevention of GBV requires attention to both demand- and supply-side factors and programming is moving toward this integration, including in Nepal. However, little research exists at the nexus of these issues. To address this gap, we provide a comprehensive mixed-methods situation analysis of GBV-related social norms, help-seeking, and S&J service provision. Methods Data included a household survey (N = 3830), a sub-study of youth (N = 143) and married adults (N = 464) in one site and qualitative data collection including interviews with S&J service providers, help-seeking GBV survivors and families (N = 68), and focus group discussions with police, youth groups, and school management committees (N = 20) in four sites. Descriptive analysis of survey data was triangulated with findings from a modified grounded theory analysis of the qualitative data to elucidate the role of social norms and other barriers limiting help-seeking. Results GBV was perceived to be common, especially child marriage, domestic violence, eve-teasing, and dowry-related violence. Formal help-seeking was low, despite positive attitudes towards S&J providers. Participants described injunctive norms discouraging formal reporting in cases of GBV and sanctions for women violating these norms. Conclusions Norms favoring family- and community-based mediation remain strong. Sanctions for formal reporting remain a deterrent to help-seeking. Leveraging gender-equitable role models, such as female S&J providers, and connecting S&J providers to women and youth may capitalize on existing shifts.